Improvement of Business Process Modeling in Internal Audit Planning at an Indonesian State-Owned Enterprise - Ardha, Novan Bastian Dwi; Riwajanti, Nur Indah; Haris, Zainal Abdul (Pusat P2M Politeknik Negeri Batam, 2025)
The previous research reported that there were gaps between the procedure of internal auditing at an Indonesian state-owned enterprise namely J Corp with the standard set by an international association of internal auditor. In order to harmonize the company's procedure with the international standard for professional practice of internal auditing, this study analyzes the current business process of internal audit planning activity and proposes the to-be business process modeling. Special attention is given to the need of internal auditors as the key users of this activity to making improvement and adjustment the future business process model. This study applied qualitative approach by conducting focus group discussion with the internal auditors, reviewing the standard operating procedure of internal auditing, and observing the walkthrough of internal audit planning that have been done by internal auditors. By using Business Process Modeling and Notation, this study will draw graphical notation to depict steps in business process of company's internal audit planning. The result of study is immediately beneficial for the internal audit function at the J Corp to improve their standard operating procedure by conforming to the international standard and also enriches the literature for practitioners to know-how to improve the business process in the internal audit planning.